ON THE BEHAVIOUR OF SOME PROBABILISTIC CHARACTERISTICS OF THE OUTPUT OF MULTIDIMENSIONAL RANDOM WALK FROM EXPANDING SETS (American Journal of Research in Humanities and Social Sciences, 2023)
This paper establishes an analog of the well-known theorem of P. J. Bickel and J. A. Yahav on the number of exits of a multidimensional random walk from expanding sets. This theorem and related problems are carried forward for the moment of the first exit.